2022
DOI: 10.1002/ehf2.13973
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+/calmodulin‐dependent protein kinase II and protein kinase G oxidation contributes to impaired sarcomeric proteins in hypertrophy model

Abstract: Aims Volume overload (VO) induced hypertrophy is one of the hallmarks to the development of heart diseases. Understanding the compensatory mechanisms involved in this process might help preventing the disease progression. Methods and resultsTherefore, the present study used 2 months old Wistar rats, which underwent an aortocaval fistula to develop VO-induced hypertrophy. The animals were subdivided into four different groups, two sham operated animals served as age-matched controls and two groups with aortocav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 79 publications
(223 reference statements)
0
1
0
1
Order By: Relevance
“…MYOM2, a member of the myomesin protein family, is a major component of the myofibrillar myogenic fiber M-band and a central gene in myofibrillar gene interactions 28 . In contrast, CaMKII is a signaling molecule whose activity is triggered by an increase in intracellular Ca 2+ levels, an activity that can be sustained by enzymatic autophosphorylation, generating molecular memory concentrations after a decrease in Ca 2+ ; it regulates a variety of proteins that are involved not only in ECC and relaxation but also in cell death, transcriptional activation of hypertrophy, inflammation, and arrhythmias 29 , 30 . We verified by Western Bloting assay and found that diacetylmorphine increased the phosphorylation level of CaMKII T287 site in cardiomyocytes and increased the relative expression of TPM1 and MYOM2 proteins compared with the con group, while after using CaMKII inhibitor KN-93, compared with the drug group, the phosphorylation level of CaMKII T287 site The relative expression of TPM1 and MYOM2 proteins was decreased.…”
Section: Discussionmentioning
confidence: 99%
“…MYOM2, a member of the myomesin protein family, is a major component of the myofibrillar myogenic fiber M-band and a central gene in myofibrillar gene interactions 28 . In contrast, CaMKII is a signaling molecule whose activity is triggered by an increase in intracellular Ca 2+ levels, an activity that can be sustained by enzymatic autophosphorylation, generating molecular memory concentrations after a decrease in Ca 2+ ; it regulates a variety of proteins that are involved not only in ECC and relaxation but also in cell death, transcriptional activation of hypertrophy, inflammation, and arrhythmias 29 , 30 . We verified by Western Bloting assay and found that diacetylmorphine increased the phosphorylation level of CaMKII T287 site in cardiomyocytes and increased the relative expression of TPM1 and MYOM2 proteins compared with the con group, while after using CaMKII inhibitor KN-93, compared with the drug group, the phosphorylation level of CaMKII T287 site The relative expression of TPM1 and MYOM2 proteins was decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Нарушение фосфорилирования отдельных частей молекулы титина или активацию под влиянием некоторых факторов (например, шаперона Hsp90, индукторов и продуктов окислительного стресса или провоспалительных цитокинов) ее дефосфорилирования серин/треонин фосфатазой 5 относят к титин-зависимым механизмам развития повышения жесткости миокарда и диастолической сердечной недостаточности [12,49,53,54,[95][96][97][98]. Поскольку дифференцированные сегменты отдельных изоформ титина в растяжимой части I-полосы могут фосфорилироваться различными протеинкиназами, что приводит к неодинаковым эффектам, выяснение статуса фосфорилирования титина важно, когда требуется всестороннее понимание механизмов изменения жесткости миокарда при развитии сердечной недостаточности с сохраненной ФВ ЛЖ [80,99].…”
Section: титин и его роль в механизмах диастолической дисфункции лево...unclassified